Determinação simultânea de sódio, potássio e cálcio em biodiesel por espectrometria de emissão atômica com chama utilizando emulsão como preparo das amostras - Juliana Divina Almeida Raposo (2010)
This work developed an analytical method for simultaneous determination of Na, K and Ca in which samples of biodiesel, in the emulsion form, were analyzed in an equipment based on the technique of atomic emission spectrometry flame in conjunction with the detector of continuous emission. The preparation of emulsions was optimized using the experimental design, and the optimal experimental conditions were: 0.4 mL HNO3 and 1.0 g of Triton X-100. Interference of transportand matrix were corrected using the element Li as internal standard and emulsified oil and inorganic standards in the preparation of the analytical curves. The method showed good linearity (R> 0.999) and relative standard deviations less than 5%. The limits of quantification of 0.32 and 0.16 mg kg-1 for Na and K, respectively, they showed high sensibility of the method for quantification of those elements in biodiesel for emulsion. However, the high quantification limit for Ca (10,8 mg kg -1), it showed low sensibility of the proposed method. The accuracy was assessed by comparing the results obtained by the reference method (NBR 15553) and interlaboratory tests, beyond recovery tests. We also compared the results of Na and K for samples of biodiesel in the form of emulsion using a photometer commercial scale. The method presented good percentile of recovery and good accuracy in the analysis of In the, Kand Ca in biodiesel samples of different oleaginous. The results were consistent with those achieved by the proposed method at 95% confidence. The use of emulsions with FAES technique was a simple strategy and low cost to evaluate the quality of biodiesel in terms of concentrations of metals Na, K and Ca.